The Coconut Fiber: USE OF COCONUT COIR WASTE AS A NATURAL REINFORCEMENT MATERIAL IN NORMAL CONCRETE - Muhammad Buttomi Masgode Buttomi (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
Until now, the utilization of coconut coir waste in Kolaka Regency, Southeast Sulawesi Province, has not been optimal, especially in the world of construction. This study aims to examine the effect of using coconut coir fiber as a natural reinforcement material in concrete. The research method is using experimental methods carried out in the laboratory. The test sample used with dimensions of 150 mm x 300 mm. There were 2 (two) types of samples used, namely normal concrete samples and concrete samples with coconut fiber reinforcement with a total sample of 30 pieces with a concrete design age of 7 days, 14 days and 28 days. After drying, 15 samples were coated with coconut fiber waste using adhesive glue, the remaining 15 samples were not given reinforcement. The results of this study obtained the compressive strength test data for normal concrete aged 7 days of 13.46 MPa and concrete with reinforcement of 11.26 MPa. At the age of 14 days the compressive strength of normal concrete is 17.55 MPa and reinforced concrete is 20.51 MPa. And, for normal concrete age of 28 days it is 22.59 MPa and concrete with reinforcement is 25.80 MPa. The conclusion of this study is that there is an increase in compressive strength for concrete with reinforcement against normal concrete from a design compressive strength of 22.5 MPa, which is 14.67%. Keyword: Natural Reinforcement, Coconut Coir, Concrete